Opiate‐Free Pain Therapy Using Carbamazepine‐Loaded Microparticles Provides Up to 2 Weeks of Pain Relief in a Neuropathic Pain Model. Issue 8 (14th June 2018) - Dai, Haining; Tilley, Dana M.; Mercedes, Greici; Doherty, Chris; Gulati, Amitabh; Mehta, Neel; Khalil, Amer; Holzhaus, Katrin; Reynolds, Francis M.
Abstract: Introduction: Opioids remain a mainstay in the treatment of acute and chronic pain, despite numerous and potentially dangerous side effects. There is a great unmet medical need for alternative treatments for patients suffering from pain that do not result in addiction or adverse side effects. Anticonvulsants have been shown to be effective in managing pain, though high systemic levels and subsequent side effects limit their widespread usage. Our goal was to determine if the incorporation of an anticonvulsant, carbamazepine, into a biodegradable microparticle for local sustained perineural release would be an efficacious analgesic following a peripheral injury. Methods: Following induction of the chronic constriction injury model in Sprague‐Dawley rats, mechanical allodynia testing was performed using von Frey filaments and thermal allodynia was evaluated using the Hargreaves method. Histology and blood work were performed to evaluate toxicity as well as to monitor drug and metabolite presence over time. Results: A 2‐fold increase in hindpaw withdrawal thresholds in animals receiving carbamazepine‐loaded microparticles relative to controls was observed for up to 14 days after treatment. Drug and metabolite had a peak blood concentration of 54.7 ng/mL and dropped off exponentially to < 5 ng/mL over a few days. Conclusion: This formulation reduced systemic exposure to carbamazepine over 1, 000‐fold relative to traditional analgesic dosing regimens. This 2‐component drug delivery system has been specifically engineered to release a controlled amount of carbamazepine over a 14‐day period, providing significant pain relief with no toxicological or observable adverse events via behavioral or histochemical analysis.